Comportamento de cultivares de feijão (Phaseolus vulgaris L) na Zona da Mata de Minas Gerais- III - Vieira , Clibas; da Silva, Corival Cândido; Chagas, José Mauro; de Andrade Araújo , Geraldo A (Revista Ceres, 2025)
The black beans (Phaseolus vulgaris) ‘Rico 23', ‘Negrito 897", ‘Costa Rica’, ‘Vene- zuela 1056', “51.051', ‘S-166-A-N’, ‘Linea 29', ‘Rio Tibagi', BAT-67, BAT-65, BAT-T5, BAT-55, and BAT-64 as well as the non-black beans “Manteigão Fosco 11", ‘Ricopardo 896’, ‘Vi. 1010', ‘Ricobaio 1014’, ‘Carioca’, ‘Diacol Calima’, and ‘Quinhentas Vagens’, were included in 17 yield trials, in nine municipalities of the Zona da Mata area, State of Minas Gerais, during two years.